Application of Problem Based Learning (PBL) to Improve English Speaking Skills - Dwiyamtini, Margaretha Rulik (Universitas Muhammadiyah Semarang, 2023)
This study aims to determine the improvement of English speaking skills through the Problem Based Learning (PBL). This research was conducted in semester 2 of 2022/2023 academic year. The research design was classroom action research carried out in two cycles for 3 months. The research subjects were students of class XI.IPA-4 at SMAN 15 Semarang, a total of 36 students. Data obtained through documentation techniques, observations and tests. The test data is processed quantitatively. And the observation data is processed qualitatively. In the initial conditions, the results of the students' speaking skill scores showed an average of 70.67, which was still less than the KKM score, which was 75. After applying the Problem Based Learning PBL learning model in cycle I, there was a slight increase in the average to 76.33 with 69% mastery. And in cycle II it becomes 82.11 with 89% mastery. The results of the study show that through the application of the Problem Based Learning (PBL), there is an improvement of English speaking skills.Keywords: Problem Based Learning, English Speaking Skills